OP0258 Efficacy of the highly selective adamts-5 inhibitor glpg1972 in the rat meniscectomy model. (12th June 2018) - Lepescheux, L.; Clement-Lacroix, P.; Merciris, D.; Meurisse, S.; Borgonovi, M.; Cottereaux, C.; Mollat, P.; Brebion, F.; Gosmini, R.; De Ceuninck, F.; Botez, I.; van der Aar, E.; et al.
Abstract : Background: Aggrecan cleavage is an early process in cartilage degradation observed in OA. As a result, aggrecanase inhibition is an attractive therapeutic strategy for the treatment of OA. 1 2 A disintegrin and metalloproteinase with thrombospondin motifs-5 (ADAMTS-5) is an aggrecanase playing a key role in the catabolic events leading to OA. 3 We previously described the pharmacological characterisation of GLPG1972, a potent, selective and orally bioavailable ADAMTS-5 inhibitor showing anti-catabolic activity in cartilage explants and displaying disease-modifying OA drug (DMOAD) potential in the destabilisation of the medial meniscus (DMM) model in mice. 4 5 Objectives: In this communication we report the activity of GLPG1972 in a second model of surgery-induced OA, the rat meniscectomy (MNX) model. 6 Methods: OA pathology was induced by meniscectomy in the right hind leg of each rat. On day 1 post surgery, rats were randomly assigned to a treatment group (n=20 per group) according to their body weight. GLPG1972 was administered orally over 3 weeks at dose levels of 10, 25 and 50 mg/kg b.i.d. At sacrifice, the right tibias were collected and processed for histological analysis. OA development in the tibial plateau was evaluated using the OARSI score. The following structural parameters were measured by imaging histomorphometry analysis: subchondral bone plate thickness, proteoglycan content and fibrillation index. Blood samples were collected at steady state at predose, 1, 3 and 6 hour postdose for the determination of GLPG1972 plasma concentrations. Results: Three weeks post-surgery, a significant reduction in OARSI score compared to vehicle-treated rats was observed with GLPG1972 at 25 and 50 mg/kg b.i.d. (−24% and −23%, respectively). Treatment with GLPG1972 also resulted in a significant reduction in cartilage fibrillation as of 25 mg/kg b.i.d. and prevented proteoglycan loss and subchondral bone plate thickening at all doses. At 25 mg/kg b.i.d. GLPG1972 average plasma concentration over 24 hour was found to be in line with the value observed in other rat MNX experiments (385 ng/mL). GLPG1972 bio-distribution in the target tissue was also determined: the average condyle to plasma ratio was found to be 0.14. Conclusions: Oral dosing with GLPG1972 in rat MNX model resulted in significant chondroprotection confirming the DMOAD potential of GLPG1972. A Phase 1 first-in-human study was successfully completed with GLPG1972 (NCT02612246 ), and a dose-escalation Phase 1b study in OA patients is ongoing (NCT03311009 ). GLPG1972 is a promising OA drug candidate and a Phase 2 program is currently under preparation. References: [1] Little CB, et al. J Clin Invest2007;117:1627–1636. [2] Larsson S, et al. Arthritis Res Ther2009;11:R92. [3] Fosang AJ. Osteoarthritis Cartilage2015;23(8):1231–1232. [4] Clement-Lacroix P, et al. OARSI congress 2017. [5] Clement-Lacroix P, et al. EULAR congress 2017. [6] Little CB, Smith MM. Curr RheumatoloRev2008;4:175–182. Disclosure of Interest: None declared